Blended Learning and its Impact on English Reading Comprehension among Thai Vocational Students - Espiritu Bersamin, Alvin; Bedoya Ulla, Mark; Saripa, Aree; Suebsom, Korawan; E. Lemana II, Henry (rEFLections, 2024)
This research aimed to assess the impact of blended learning on the English reading comprehension abilities of second-year Thai vocational students. It also examined how these students perceived their satisfaction regarding their blended learning experience using the Community of Inquiry (CoI) framework. Thirty students enrolled in a Thai vocational college in the southern part of Thailand during the second semester of the Academic Year 2022-2023 participated in the study. These students attended a six-week blended learning (BL) program in which they took a one-group pretest and posttest experimental design. The BL program comprised nine lesson plans, English reading comprehension tests, and online satisfaction items. Data analysis involved paired sample t-tests, mean, and standard deviations. The findings revealed that the posttest scores for English reading comprehension were significantly higher than the pretest scores at a significance level of 0.05. Furthermore, students reported a high mean score of 4.73 (very satisfied) with their blended learning experience after their improved English reading comprehension tests. Implications were discussed, and recommendations were also offered.